TI_GERICHTE 11.2020.142 vom 19. Oktober 2021 , Ipoteca legale degli artigiani e imprenditori: noleggio di impalcature - TI Tribunale d'appello (2021)
Ipoteca legale degli artigiani e imprenditori: noleggio di impalcature